Next Generation Design and Verification Methodologies for Distributed Embedded Control Systems Proceedings of the GM R&D Workshop, Bangalore, India, January 2007 - Ramesh, S.; Sampath, P. (Springer Netherlands : Imprint: Springer, 2007)
This volume is the proceedings of the workshop "Next Generation Design and Verification Methodologies for Distributed Embedded Control Systems" organised by General Motors R&D, India Science Lab. The workshop was held on January 5-6 2007 at the NIAS auditorium, IISc campus, Bangalore, India. This workshop is the first of its kind to be organised by an automotive major to bring together the leaders in the field of embedded systems development to present state-of-the-art work, and to discuss future strategies for addressing the increasing complexity of embedded control systems. The workshop consisted of invited talks given by leading experts and researchers from academic and industrial organizations. The workshop covered all areas of embedded systems development and in particular: Formal specification and verification of distributed, heterogeneous, embedded systems Formal semantics of modeling languages Model-based specification and testing Formal approach to component based development Software product line engineering Automatic code generation for distributed, embedded systems.